Awareness of breast feeding practices amongst women visiting government hospital at Ahmedabad - Sanghvi, Ankushi A.; Pathak, Stuti D.; Nanavaty, Dhairya P.; Mehta, Manav S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Breastfeeding plays a very vital role in the overall health and development of a child. Breast milk has all the necessary nutrients required for the growth and well being of the child. It has been shown to have a protective role against various infectious and non-infectious diseases. The key elements are initiation of breastfeeding, exclusive breastfeeding for the first 6 months of life and continued breastfeeding for 2 years along with other sources of nutrition. Methods: A questionnaire based cross sectional study was conducted at a tertiary care teaching hospital. Mothers with children less than 10 years of age were included in the study. Results: Out of 150 women who were included in the study, maximum (59.33%) were in the age group of 19-26 years with the mean age being 25.7 years. 20% of women were illiterate, and a majority of them (68%) were Hindu. 115 (76.66%) mothers gave colostrum to the newborns, whereas 35 (23.33%) discarded colostrum. Also, 44% of mothers gave pre-lacteal feeds, whereas 56% of mothers didn't give pre-lacteal feeds. A significant association between initiation of breastfeeding was found with education, X2=12.63 (p<0.01). Conclusions: Our study concluded that initiation of breastfeeding within the first hour of life and colostrum feeding in the study population was lower than the WHO recommendation. Prelacteal feeding is still being practiced extensively, and that educated mothers are more likely to initiate breastfeeding within one hour of life.